2017
DOI: 10.1186/s13104-017-2507-y
|View full text |Cite
|
Sign up to set email alerts
|

In vitro quality evaluation of leading brands of ciprofloxacin tablets available in Bangladesh

Abstract: BackgroundCiprofloxacin is a broad-spectrum antibiotic that acts against a number of bacterial infections. The study was carried out to examine the in vitro quality control tests for ten leading brands of ciprofloxacin hydrochloride 500 mg tablet formulation, registered in Bangladesh by Directorate General of Drug Administration. The quality control parameters of ten different brands of ciprofloxacin hydrochloride 500 mg tablets were determined by weight variation, friability, hardness, disintegration, dissolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 21 publications
4
35
0
Order By: Relevance
“…However, five brands (71%) failed to fulfill the quality control standards. These findings are similar to those of previous studies in Rwanda and Bangladesh, which revealed that the existence of substandard formulations at purchase time is due to manufacturers' errors (9,27,22). On the contrary, these findings are not in line with previous studies from Yemen, Rwanda and Tanzania, which did not find substandard formulations at purchase time (12,23).…”
Section: Discussionsupporting
confidence: 81%
“…However, five brands (71%) failed to fulfill the quality control standards. These findings are similar to those of previous studies in Rwanda and Bangladesh, which revealed that the existence of substandard formulations at purchase time is due to manufacturers' errors (9,27,22). On the contrary, these findings are not in line with previous studies from Yemen, Rwanda and Tanzania, which did not find substandard formulations at purchase time (12,23).…”
Section: Discussionsupporting
confidence: 81%
“…Microsoft Office 2010, Sigma plot 14.0 software, and Excel 2010 were used for determination of the following parameters: area under dissolution curve (AUC), mean dissolution time, dissolution efficiency (DE), difference factor (f 1 ), and similarity factor (f 2 ). The selected generic and innovator products were subjected to weight variation, friability, and hardness tests according to the methods described by the United States Pharmacopeia (10,21).…”
Section: Methodsmentioning
confidence: 99%
“…drug's share in the global pharmaceutical market is approximately 10%, which is estimated to be increased to 25% in developing countries and may increase to 50% in certain poor countries. The FDA has reported that in poor countries, approximately 25% of drugs available for the consumers are either substandard or counterfeit drugs (10). Moreover, according to WHO, the annual trade from fake medicines are about 73 billion Euros (13).…”
Section: Assessment Of Physicochemical Properties and Comparison Of Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Quality is sustainability of drugs for their desired use measured by their efficiency, safety, consistent with label claim, or endorsed their conformity to specifications concerning identity, strength, purity and other characteristics [8]. According to International Organization for Standardization, quality control (QC) is the operational techniques and activities that are used to fulfill requirements for quality [9].…”
Section: Introductionmentioning
confidence: 99%